The Research Study of Ghulam Rabbani Agro’s Services In Sindhi Literature - Ali Jalbani, Zulfiqar (sourcecoder, 2022)
Ghulam Rabbani Agro occupies Praise worthy position in the galaxy of sindh writers. He worked for enriching sindh literature and language and did his level best for bringing better change in the society by virtue of his works. His publications consists of various literary forms such as “biographies” “Travelogues” and short stories, But his short stories and other works have not been researched and studied according to the latest research methodology, though, his work is out standing and wonderful. The topic under study will be some sort of high lighting his work on story writing. In prevailing literary, cultural and other conditions it will also pave way for further study on Subject. History and progress of short story in Sindhi literature special efforts will by take to evaluate the works of Ghulam Rabbani Agro. With special reference to crafts and message of his short stories and other writers, it will enable the researcher to determine the position and rank of Ghulam Rabbani Agro in the history of Sindhi literature.